Kolaborasi Kantor Pertanahan Kota Medan dengan Kelurahan Padang Bulan Selayang I dan Kelurahan Pangkalan Masyhur dalam Percepatan Sertifikasi Tanah Masyarakat Melalui Program Pendaftaran Tanah Sistematis Lengkap (PTSL) - Ribkha Esteria Sinaga; Wiro Oktavius Ginting (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Complete Systematic Land Registration (PTSL) a national program by the Ministry of ATR/BPN aimed at giving land ownership certificates to all Indonesians on a massive scale and at a very low cost. Although this program has been running since 2017, its implementation still faces various obstacles to collaboration, such as the lack of optimal planned and sustainable coordination mechanisms, limitations of cross-agency communication forums to the village level, lack of integrated use of communication media, and administrative problems in the community, especially related to heirs. This study aims to analyze the form of collaboration between the Medan City Land Office and the Urban Village, especially Padang Bulan Selayang 1 Village and Pangkalan Masyhur Village in accelerating land certification through the program Complete Systematic Land Registration (PTSL). This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. Data analysis used collaborative governance indicators from Ansell and Gash (2008), namely initial conditions, facilitative leadership, institutional design, collaborative processes, and interim results. The research informants consisted of the Head of the PTSL Adjudication Team, judicial officers, survey officers, village heads, neighborhood heads, and the community. The results of the study show that the collaboration between the Medan City Land Office and Padang Bulan Selayang I Village and Pangkalan Masyhur Village is realized through a clear division of tasks, direct communication in the field, and facilitative leadership support. However, obstacles were still found in the land office and the two villages in the form of the absence of a routine coordination agenda, limitations of inter-agency communication forums, lack of reporting or evaluation mechanisms in the field on an ongoing basis, and community administration problems such as inheritance problems. Nevertheless, the collaboration has contributed to an increase in the number of land certificates that have been issued, the acceleration of land administration services, and an increase in public trust in the PTSL program. This study concludes that the implementation of collaborative governance in the PTSL program in Padang Bulan Selayang 1 Village and Pangkalan Masyhur Village has been quite effective, but it still requires strengthening coordination, communication, and institutional capacity to support the sustainability of collaboration with the Medan City Land Office.